2016
DOI: 10.3389/fimmu.2016.00032
|View full text |Cite
|
Sign up to set email alerts
|

Starved and Asphyxiated: How Can CD8+ T Cells within a Tumor Microenvironment Prevent Tumor Progression

Abstract: Although cancer immunotherapy has achieved significant breakthroughs in recent years, its overall efficacy remains limited in the majority of patients. One major barrier is exhaustion of tumor antigen-specific CD8+ tumor-infiltrating lymphocytes (TILs), which conventionally has been attributed to persistent stimulation with antigen within the tumor microenvironment (TME). A series of recent studies have highlighted that the TME poses significant metabolic challenges to TILs, which may contribute to their funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 88 publications
0
80
0
1
Order By: Relevance
“…Dysregulated cancer cell growth can lead to tumor intrinsic immunosuppressive features, such as regions of hypoxia and elevated levels of lactate that can inhibit effector T cell function 34 . However, the majority of immune suppression is due to the presence of normal immune regulatory cells and molecules within the tumor that inhibit T-cell priming or suppress cytotoxic T cell function 35, 36. Of these, immune checkpoint–related molecules have garnered the most attention, with proven clinical success of ICIs.…”
Section: Immune System and Cancermentioning
confidence: 99%
“…Dysregulated cancer cell growth can lead to tumor intrinsic immunosuppressive features, such as regions of hypoxia and elevated levels of lactate that can inhibit effector T cell function 34 . However, the majority of immune suppression is due to the presence of normal immune regulatory cells and molecules within the tumor that inhibit T-cell priming or suppress cytotoxic T cell function 35, 36. Of these, immune checkpoint–related molecules have garnered the most attention, with proven clinical success of ICIs.…”
Section: Immune System and Cancermentioning
confidence: 99%
“…Hypoxia is generally considered to be immunosuppressive, although previous studies employing HIF1α, VHL-, and PHD-deficient T cells have revealed that the role of these proteins in T-cell differentiation and function is likely complex (7,8). Studies with ‘true’ hypoxia remain unclear, as apparent roles for oxygen tension in differentiation versus effector function can be disparate (9).…”
Section: Introductionmentioning
confidence: 99%
“…CPT1, as the rate-limiting enzyme in FAO, is critical for the metabolism of FAO. The phosphorylation of ACC1/2 and SREBP-1c inhibits FAS but activates FAO [90].…”
Section: Amp-activated Protein Kinasementioning
confidence: 99%
“…A previous study reported that changes in T cell metabolic regulation inhibit the antitumor capability of T cells, leading to tumor escape [88]. In the tumor microenvironment, metabolic interference and nutrients competition exist between cancer and T cells, which are important to drive cancer development [89,90]. Tumor cells require a large amount of energy metabolism to proliferate by increasing glycolysis and glucose uptake from the surrounding environment [91].…”
Section: Tumor Microenvironment and T Cell Metabolismmentioning
confidence: 99%